2022
DOI: 10.3389/fpubh.2022.994619
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trends in the burden of inflammatory bowel disease in China over three decades: A joinpoint regression and age-period-cohort analysis based on GBD 2019

Abstract: BackgroundTo study the corresponding strategies to control inflammatory bowel disease (IBD), a comprehensive assessment of the disease burden is required. Herein, we present long-term trends in the burden of IBD in China over the last three decades, as well as its epidemiological features.MethodsWe characterized the burden of IBD in China using the GBD 2019 methods and results, based on prevalence, incidence, mortality, years lost (YLLs), years lived with disability (YLDs), and disability-adjusted life years (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…YLDs are calculated by summing the frequency (prevalence), severity (weight of disability), and duration of a condition. The reliability of GBD data has been confirmed by previous studies [1421].…”
Section: Methodssupporting
confidence: 82%
See 2 more Smart Citations
“…YLDs are calculated by summing the frequency (prevalence), severity (weight of disability), and duration of a condition. The reliability of GBD data has been confirmed by previous studies [1421].…”
Section: Methodssupporting
confidence: 82%
“…In our study, the trend observed for age change was similar to that reported in our Fourth National Oral Health Survey[25], thus suggesting the validity and reliability of the study, which used GBD data. Although there are some differences in the disease burden of edentulism in terms of gender, previous studies have shown that because edentulism is associated with many factors, more studies are needed to confirm this despite the fact that the disease burden of edentulism is known to be higher in females than in males[14]; in the present study, we found that this difference was statistically significant [14].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first study that predicted the numbers and rates of IBD incidence and mortality in China in the next 25 years. Very recently, Zhang et al ( 18 ) updated the long-term trends of IBD burdens in China based on the same database GBD 2019. However, they did not provide any evaluation of future trends, which is critical for policy making.…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, the respective prevalence and incidence rates were 16.7 and 1.4 per 100,000 population in 2015 [ 27 ], and the annual percentage change in the increasing incidence of IBD from 1998 to 2008 has been estimated to be 4% to 5% [ 23 ]. In China, it was reported that the age-standardized incidence and prevalence both increased by approximately 2.5-fold within a period of 30 years from 1990 to 2019 [ 29 ]. Asian immigrants to Western countries also experience an increasing incidence of IBD [ 30 ].…”
Section: Introductionmentioning
confidence: 99%